ETIKA PENGGUNAAN MEDIA SOSIAL DAN DIGITALISASI BAGI UMKM DI KELURAHAN MIJEN KOTA SEMARANG - Amsar, Amsar; Soegiastuti, Janti (STIE Pelita Nusantara, 2023)
Social media is platform or means of digital communication that allow individuals and groups to interact, share information, and participate in online activities. Social media have become an integral part of the daily lives of many people around the world, and they have a huge impact in various fields, including communications, marketing, politics, and culture. However, the use of social media can also involve risks such as online privacy, security data, and the spread of false or inaccurate information. Promoting the use of social media and digitalization wisely is very necessary, especially for MSMEs that conduct business online so that undesirable things do not happen related to statutory regulations. Keywords: Keywords: social media, digitalization, and MSMEs